Sibiu Tourist Destination Sustainability Analysis Based On Visitors' Perception Using The European Tourism Indicators System - Elena Manuela ISTOC; Mihaela Adina MATEESCU; Mihai Sabin MUSCALU; Daniela Nicoleta BALEANU (Communications of International Proceedings, 2022)
The transition to more sustainable forms of development is one of the major trends and challenges in our times and despite the popularity of sustainable tourism, there is still much to be done. The gap between the theoretical concept of sustainable development and its actual implementation in the real world is growing. Therefore, it is crucial to find methods of monitoring that support the development of sustainable tourism in destinations.This paper provides an overview of the sustainability of the tourist destination "Sibiu County " from the perspective of visitors based on the application of the European Tourism Indicators System.
Keywords: Tourist Destination; Sustainable Development; Visitors’s Perception; Quantitative Research; European Tourism Indicators System